A Genetic Variant of miR-34a Contributes to Susceptibility of Ischemic Stroke Among Chinese Population - Wei, Gui-Jiang; Yuan, Ming-Qing; Jiang, Li-He; Lu, Yu-Lan; Liu, Chun-Hong; Luo, Hong-Cheng; Huang, Hua-Tuo; Qi, Zong-Quan; Wei, Ye-Sheng (Frontiers in Physiology, 2019)
MiRNAs are small non-coding RNAs modulating gene expression, and variants in miRNA genes involve the pathogenesis of ischemic stroke (IS). However, the effect of miR-34a polymorphisms on IS susceptibility has been rarely reported. In the present study, we investigated the association between rs12128240, rs2666433 and rs6577555 in the miR-34a gene and IS susceptibility. Snapshot assay was used to detect miR-34a polymorphisms in 548 IS patients and 560 controls. Relative expression of miR-34a was measured by quantitative real-time PCR. We found that rs2666433 was associated with a significantly increased risk of IS (AA vs. GG: OR=1.61, 95% CI=1.05-2.52, P=0.031; AA vs. GG+GA: OR=1.58, 95% CI=1.05-2.45, P=0.026). Of the IS subtypes, rs2666433 was associated with large artery atherosclerosis (AA vs. GG: OR=2.09, 95% CI=1.16-3.51, P=0.007; AA vs. GG+GA: OR=2.02, 95% CI=1.15-3.33, P=0.007; A vs. G: OR=1.36, 95% CI=1.07-1.81, P=0.021). Additionally, the level of miR-34a was significantly up-regulated in IS patients compared to the controls (P<0.001), and the patients with rs2666433 AA genotype had a higher level miR-34a than those with GG+GA genotypes (P<0.001). Furthermore, increased level of homocysteine was shown in IS patients compared to the controls (P<0.001), and in patients carrying the rs2666433AA compared to those carrying the rs2666433 GG+GA (P<0.001). However, no significant association of rs12128240 or rs6577555 with IS was found. Collectively, our study found the association between miR-34a polymorphisms and the risk of IS among the Chinese population. The results may provide an explanation for etiology of IS and a potential biomarker or therapeutic target for IS.